Financial development and economic growth: A meta-analysis - Petra Valíčková; Tomáš Havránek; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2013)
We analyze 1334 estimates from 67 studies that examine the effect of financial development on economic growth. Taken together, the studies imply a positive and statistically significant effect, but individual estimates vary a lot. We find that both research design and heterogeneity in the underlying effect play a role in explaining the differences in results. Studies that do not address endogeneity tend to overstate the effect of finance on growth. While the effect seems to be weaker in poor countries, the effect decreases worldwide after the 1980s. Our results suggest that stock markets support faster economic growth than other financial intermediaries. We find no evidence of publication bias in the literature.
Keywords: C83; G10; O40; 330; finance; development; growth; meta-analysis